Deposit-refund systems and the interplay with additional mandatory extended producer responsibility policies - Laubinger, Frithjof (OECD Publishing, 2022)
Despite decades of experience with Deposit Refund Systems (DRS) in some countries and sub-national markets, there are only a few instances where DRS is complemented by additional mandatory extended producer responsibility (EPR) policy instruments within the same sector. In light of increasingly ambitious collection and recycling targets, countries and sub-national governments are considering the use of a DRS for specific products in combination with other mandatory EPR policy instruments. This interplay of a DRS and other mandatory EPR policy instruments can lead to synergies, as it can improve the quality and quantity of recycling, enable reuse systems and incentivise eco-design. DRS also helps to address littering and influence consumer behaviour, which is difficult to address with other mandatory EPR policy instruments. This report identifies key insights that can guide the design and implementation of a DRS and its role in a broader policy mix including other mandatory EPR policies
Keywords: Environment